Chitin synthase 3 from yeast has zymogenic properties that depend on both the CAL1 and the CAL3 genes. - Choi, W J (1994)
In previous studies, chitin synthase 3 (Chs3), the enzyme responsible for synthesis of most of the chitin present in the yeast cell, was found to be inactivated by incubation with trypsin, in contrast to other yeast chitin synthases (Chs1 and Chs2), which are stimulated by this treatment (chitin synthase; UDP-N-acetyl-D-glucosamine:chitin 4-beta-N-acetylglucosaminyl-transferase, EC 2.4.1.16). It has now been found that the substrate UDPGlcNAc protects Chs3 against proteolytic inactivation. Treatment of Chs3-containing membranes with detergents drastically reduced the enzymatic activity. Activity could, however, be restored by subsequent incubation with trypsin or other proteases in the presence of UDPGlcNAc. Under such conditions, protease treatment stimulated activity as much as 10-fold. A change in divalent cation specificity after trypsin treatment suggests that the protease directly affects the enzyme molecule. Experiments with mutants in the three genes involved in Chs3 activity--CAL1, CAL2, and CAL3--showed that only CAL1 and CAL3 are required for the protease-elicited (zymogenic) activity. It is concluded that Chs3 is a zymogen and that the CAL2 product functions as its activator. The differences and possible similarities between Chs3 and the other chitin synthases are discussed.